2003
DOI: 10.1074/jbc.m212590200
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Heparan Sulfate (HS) in FGF1/HS/FGFR1 Signaling Complex

Abstract: Fibroblast growth factor (FGF) signaling begins with the formation of a ternary complex of FGF, FGF receptor (FGFR), and heparan sulfate (HS). Multiple models have been proposed for the ternary complex. However, major discrepancies exist among those models, and none of these models have evaluated the functional importance of the interacting regions on the HS chains. To resolve the discrepancies, we measured the size and molar ratio of HS in the complex and showed that both FGF1 and FGFR1 simultaneously interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 57 publications
(85 reference statements)
5
129
0
3
Order By: Relevance
“…Moreover, it has been shown that with the assistance of heparin, either dimerization of FGF1 or of FGFRs precedes the FGF1-FGFR binding in a 2:2 ternary fashion. [30][31][32] Therefore, both the self-assembly and heparin-binding qualities of the fibronectin part might facilitate the FGF1-FGFR interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that with the assistance of heparin, either dimerization of FGF1 or of FGFRs precedes the FGF1-FGFR binding in a 2:2 ternary fashion. [30][31][32] Therefore, both the self-assembly and heparin-binding qualities of the fibronectin part might facilitate the FGF1-FGFR interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Gel Mobility Shift Assay (GMSA)-NRG1 alone or NRG1 plus various heparins at various concentrations were incubated with binding buffer (2.7 mM KCl, 4.3 mM Na 2 HPO 4 , 10 mM MgCl 2 , 1.4 mM KH 2 PO 4 , 12% glycerol, 1 mM dithiothreitol) for 20 min and run on a 6% (29:1 acrylamide:bis) non-denaturing gel (10 mM Tris, pH 7.4, 1 mM EDTA) for 20 min at 200 V as described previously (30,31). Although the electrophoresis buffer consisted of 40 mM Tris, pH 8.0, 40 mM acetic acid, 1 mM EDTA, changing the pH to 9.0 above the isoelectric point of NRG1 (pI ϭ 8.8) did not appreciably change the mobility of NRG1 with or without added heparin.…”
Section: Methodsmentioning
confidence: 99%
“…HSPGs include cell surface transmembrane proteins (syndecans), cell surface glycerophosphatidylinositide-anchored proteins (glypicans), and diffusible protein components of the extracellular matrix (perlecan and agrin) (Ornitz and Itoh 2015). Cell surface and extracellular matrix HSPGs affect diffusion of FGFs in tissues and interact with FGFs and FGFRs to increase the affinity of FGF-FGFR heterodimers to enhance receptor activation (Wu et al 2003;Belov and Mohammadi 2013;Xu and Esko 2014). In contrast to canonical FGFs, endocrine FGFs require a protein cofactor to enhance receptor binding and activation.…”
Section: Fgf Signalingmentioning
confidence: 99%